2019
DOI: 10.1111/irv.12700
|View full text |Cite
|
Sign up to set email alerts
|

State‐level estimates of excess hospitalizations and deaths associated with influenza

Abstract: Background National estimates of influenza burden may not reflect state‐level influenza activity, and local surveillance may not capture the full burden of influenza. Methods To provide state‐level information about influenza burden, we estimated excess pneumonia and influenza (P&I) and respiratory and circulatory (R&C) hospitalizations and deaths in Colorado from local hospital discharge records, death certificates, and influenza virus surveillance using negative binomial models. Results From July 2007 to Jun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 25 publications
4
21
0
Order By: Relevance
“…In line with previous studies 6, [48][49][50] , influenza-associated mortality rate was found the highest among adults aged ≥ 65 years. Our pooled influenza-associated respiratory mortality rate (5.84 per 100,000 persons) fell within the estimate for the Western Pacific region reported in a global study (3.6-7.5 per 100,000 persons) 2 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with previous studies 6, [48][49][50] , influenza-associated mortality rate was found the highest among adults aged ≥ 65 years. Our pooled influenza-associated respiratory mortality rate (5.84 per 100,000 persons) fell within the estimate for the Western Pacific region reported in a global study (3.6-7.5 per 100,000 persons) 2 .…”
Section: Discussionsupporting
confidence: 92%
“…Our pooled estimates were also comparable with the corresponding estimates published for other countries or regions; e.g. our pooled excess all-cause mortality rate (14.33 per 100,000 persons) was similar to those reported in Europe (13.30 per 100,000 persons) 48 and Hong Kong SAR (11.70 per 100,000 persons) 6 , but slightly higher than that reported in the USA (6.96 per 100,000 persons) 49 and South Korea (5.97 per 100,000 persons) 50 . Our influenza-associated P&I (384 per 100,000 persons) or SARI (442–715 per 100,000 persons) hospitalization rate among children aged < 5 years was much higher than those reported for Singapore (excess P&I hospitalization rate of 186.8 per 100,000 persons) 51 , Portugal (excess P&I hospitalization rate of 42.6 per 100,000 persons) 52 , Chile (excess SARI hospitalization rate of 71.5 per 100, 000 persons) 53 .…”
Section: Discussionsupporting
confidence: 91%
“…To estimate the burden of death due to novel respiratory pathogens, previous studies have compared the observed incidence of influenza-related deaths ascribed to pneumonia and influenza (“P&I”) with the baseline incidence of P&I that would be expected at that time of year. 5, 6 These “excess deaths” provide an estimate of pathogen-specific burden. This approach was used in the early months of the 2009 influenza A/H1N1-pdm pandemic; it was estimated that just 1 in 7 pandemic-related deaths was captured by laboratory testing in 2009 in the US.…”
Section: Introductionmentioning
confidence: 99%
“…We obtained estimates for seasonal influenza-and RSV-attributable cardiorespiratory hospitalizations by fitting negative binomial regression excess models, a method commonly used in surveillance studies. 8,31,32 Candidate models that were fit and compared consisted of different linear combinations of ( 1 E(Y i ) = α × exp β lag(H1N1pdm09) i + β 7 lag(H3N2) i + β 8 lag(B) i + β 9 lag(RSVpcr) i ( )…”
Section: Discussionmentioning
confidence: 99%
“…In particular, influenza and RSV infections commonly have cardiorespiratory sequelae that include acute myocardial infarction, stroke, and exacerbation of asthma and chronic obstructive pulmonary disease. [4][5][6] Although evidence of the incidence and risk factors for influenza and RSV infections among older adults is starting to emerge, 4,[7][8][9][10][11][12][13][14] little is known about the implications of these respiratory viruses for the most vulnerable group: residents of long-term care facilities (LTCFs).…”
Section: Introductionmentioning
confidence: 99%